2021
DOI: 10.1111/ijcp.14651
|View full text |Cite
|
Sign up to set email alerts
|

Serum miR‐224, miR‐760, miR‐483‐5p, miR‐378 and miR‐375 as potential novel biomarkers in rheumatoid arthritis

Abstract: Background Rheumatoid arthritis (RA) is an inflammatory autoimmune disease which affects various tissues and organs mainly joints. Serum microRNAs are considered a new class of non‐coding RNA which plays a vital role in pathogenesis of RA. Methods The current study was conducted on 80 RA patients and 80 healthy participants. Serum expression levels of miR‐224, miR‐760, miR‐483‐5p, miR‐378 and miR‐375 were evaluated via real‐time quantitative polymerase chain reaction (PCR). Results Significant upregulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…This result suggests that miR-378a-5p may play a vital role in the pathogenesis of RA and function as a potential therapeutic target for RA. On the contrary, recent studies have shown a significant increase in the expression of miR-378a-5p in the serum of RA patients [ 62 ] and in the synovial tissue of patients with osteoarthritis who have undergone an extra-articular implant [ 63 ]. Furthermore, a high enrichment of miR-378a-5p was found in EVs derived from MSCs, which could contribute to the attenuation of colitis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that miR-378a-5p may play a vital role in the pathogenesis of RA and function as a potential therapeutic target for RA. On the contrary, recent studies have shown a significant increase in the expression of miR-378a-5p in the serum of RA patients [ 62 ] and in the synovial tissue of patients with osteoarthritis who have undergone an extra-articular implant [ 63 ]. Furthermore, a high enrichment of miR-378a-5p was found in EVs derived from MSCs, which could contribute to the attenuation of colitis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-23b levels were found to be significantly elevated in the synovial tissue cells and plasma of RA patients and positively correlated with platelet (PLT) counts, CRP, hypersensitive-CRP (hs-CRP), ESR, and DAS28 ( p < 0.05), and treatment reversed the trend of elevated plasma miR-23b levels ( 107 ). Moreover, miR-23 could regulate CXCL12 through the NF-κB signaling pathway to suppress the inflammation involved in RA pathogenesis ( 108 ).…”
Section: Candidate Rnas As Biomarkers For Ramentioning
confidence: 99%
“…Concentration of circulating miR-23b , which positively correlates with ESR, CRP, and DAS-28, is significantly up-regulated after appropriate treatment, indicating that miR-23b is a dual marker for disease activity and prognosis ( 105 ). Similarly, miR-96-5p, miR-134-5p, miR-140-3p, miR-627-5p, miR-224, miR-760, miR-483-5p, miR-378, and miR-375 are not only diagnostic markers for RA, but also mirror disease activity ( 106 , 107 ). However, these studies are still descriptive.…”
Section: Blood and Serum-circulating Mirnas Provide Novel Opportuniti...mentioning
confidence: 99%